2005
DOI: 10.1007/s11661-005-0303-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of nanostructured spherical aluminum oxide powders by plasma engineering

Abstract: Irregularly shaped aluminum oxide particles were plasma atomized resulting in narrow size range distribution of spherical nanostructured powders. Cooling rates, on the order of 10 6 to 10 8 K/s, were obtained from the different quenching medias, viz. air, water, and liquid nitrogen. Plasma-engineered powder particles developed nanosize crystallites, while solidification provided insight into the morphological feasibility in refinement of grain size. X-ray diffraction (XRD) methods have been used to quantify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Cooling rates were estimated from the XRD spectrum (Fig. 5) using full‐width at half‐maximum (FWHM) peak intensity, and also the crystallite size is determined from the peak characteristic as follows 6,7,21,22 : where is average crystallite size, k is shape factor (∼0.9), λ is wavelength, ( B − b ) is FWHM, θ is angle of diffraction, Q is the average cooling rate, n is cooling rate exponent (∼0.32), c is a material‐dependent constant (∼34) 6–7,21,22 . Average crystallite size was calculated to be approximately 60–90 nm in diameter, which matches with the crystallite size observed in the TEM images.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cooling rates were estimated from the XRD spectrum (Fig. 5) using full‐width at half‐maximum (FWHM) peak intensity, and also the crystallite size is determined from the peak characteristic as follows 6,7,21,22 : where is average crystallite size, k is shape factor (∼0.9), λ is wavelength, ( B − b ) is FWHM, θ is angle of diffraction, Q is the average cooling rate, n is cooling rate exponent (∼0.32), c is a material‐dependent constant (∼34) 6–7,21,22 . Average crystallite size was calculated to be approximately 60–90 nm in diameter, which matches with the crystallite size observed in the TEM images.…”
Section: Resultsmentioning
confidence: 99%
“…Vacuum plasma spray formed tantalum carbide (TaC) provides an alternative to overcome fabrication hurdle of high melting point materials and their brittleness. Plasma plume reaches temperatures in excess of 10 000 K and impacts the powders in molten or semi‐molten states generating typical mechanically bonded layered structure 4,6,7 . It is important to emphasize that much of the literature research material for the applications of TaC, because of military applications, is sparingly available 4,8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Survival of CNTs was possible because of rapid kinetics inherent to the plasma spray processing. Laha et la has investigated CNT/metal interface in Al-Si/CNT system [43,44,118]. It was concluded that a thin layer of SiC on CNT is formed ( Fig. 2.21b) suggesting interfacial reaction which improved interface wettability required for .t-AI-Si matrix x 1 .…”
Section: Cnt Reinforced Metal Matrix Nanocompositesmentioning
confidence: 99%
“…Basic challenge arising in the metal-CNT nanocomposite is associated with damage to CNTs at high temperature processing, as required for metal processing [43,44,118]. Secondary challenge includes low interfacial bonding strength between CNT and metal interface [156][157][158].…”
Section: Cnt Reinforced Metal Matrix Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation